Where do foreign firms locate in France and why? - Thierry Mayer (EIB Papers, 2004)
This paper studies the determinants of individual location choices of manufacturing production units by foreign affiliates. It concentrates on the specific case of FDI location in France over the period from 1985 to 1995 and evaluates, in particular, how regional policies in favour of French regions by both national and EU authorities compare to other determinants of the location choice. It is shown that foreign investors are, to a large extent, not sensitive to public investment incentives, and are primarily driven by conventional forces such as the market potential, labour costs and agglomeration effects in the region considered for investment. Proximity to the home country of the investor also has a robust positive effect on location choice.
Keywords: 330; Direktinvestition; Betriebliche Standortwahl; Investitionspolitik; Arbeitskosten; Agglomerationseffekt; Frankreich; Marktpotential